Getting serious about the challenge of regulating germline gene therapy - Caplan, Arthur (PLoS biology, 2019)
The announcement of He Jiankui's germline editing of human embryos has been followed by a torrent of almost universal criticism of the claim on scientific and ethical grounds. That criticism is warranted. There is little room for anything other than vociferous condemnation of He's announcement. Presenting the results of groundbreaking work by press conference and YouTube is not science. The issue now is not whether the work supporting the claims reported from China was done in an ethical manner. It was not. What is required to move forward is a justification for doing germline editing in humans. Many think there is none, and prohibitions abound. If such work is justifiable, a serious, rigorous framework must be imposed that insures that such research is done following the highest ethical standards that both protect human subjects and insure public trust and support.